I kin sea slugs: awkward kin, inhuman horror, and queering encounter in Octavia Butler's Dawn - Witter, Genevieve, author; Badia, Lynn, advisor; Claycomb, Ryan, committee member; Chatterjee, Sushmita, committee member (Colorado State University. Libraries, 2023)
Anthropocentrism is rooted in narratives of evolutionary teleology and the human/nonhuman binary which exalts the human, homo sapiens, as the dominant Earth species, and taxonomizes nonhuman species according to human value systems. Octavia Butler's science-fiction novel, Dawn, raises important questions about the human as an identity category, according to anthropocentrism, and as a species. By introducing a multispecies encounter with an extraterrestrial species, Butler troubles our understanding of what it means to be human. Butler queers human-centric notions of ecology and evolutionary teleology through her protagonist, Lilith, as she attempts to adapt to a radically different, and at times hostile, environment. Lilith's horror for both the Oankali, humanity's alien rescuers, and the potential for an inhuman future, prompted by a hybrid-species zygote, introduce an opportunity to dissect human abjection for the non-/in-human and to overcome anthropocentric discomfort with human vulnerability to the nonhuman. Joining the conversation with Lee Edelman's theory of reproductive futurity, Donna J. Haraway's concept of sympoiesis, and Julia Kristeva's essay on abjection, this argument examines Lilith's fear for the inhuman to discuss the ways in which anthropocentric ideology jeopardizes humanity's ability to take action amidst the worsening climate crisis. As nonhuman Earth species' fate becomes increasingly tied to humanity's ability to responsibly address climate change, we need to reevaluate the way that humanity situates itself in multispecies Earth ecologies.
Keywords: horror; multispecies; transcorporeality; literature; ecology; queer